(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The study of language, culture and translation and the relationship between them are crucial issues because of the importance of human communication in the world. Language is viewed as the main factor that links different cultures of different nations and a way of expressing feelings, thoughts and ideas that people try to convey. Language and culture are closely related to each other. Language is considered as a part of culture of a particular community and the main way by which the members of a society communicate with each other. The variety of languages with different cultures and necessity of communications in human life caused translation to be a very effective factor in communicating, exchanging cultures, and knowledge. Thus, it seems that language and culture are closely related and it is essential to consider both in the process of translation. Therefore, this paper aims to focus on concept of culture from different viewpoints in translation studies and to offer an analysis of researchers’ views of the interaction between culture and language and also between culture and translation. Furthermore, we know that translation plays an important role of crossing through different cultures and communication. Therefore, it is said that translation is one of the essential, fundamental, and adequate ways in transferring culture. However, the translator encounter many different types of challenges because in order to translate properly, a good translator should have knowledge not only about linguistic components but also about cultural elements, views, customs and tradition in order to take into consideration the chronological orders, historical and religious background of the source text. Lastly, what is the most essential point is the transmission of the same message as the source text attempted to and avoid adding irrelevant words into language used by people.